Factors Associated With the 30-day Readmission Rate in Patients With Heart Failure - Fereshteh Rezvani; Zahra Abbasi Dolatabadi; Maryam Esmaeili; Saman Maroufizadeh; Mohammad Garakyaraghi; Monir Mazaheri (Journal of Holistic Nursing and Midwifery)
Introduction: Heart failure (HF) is a complex and common clinical syndrome whose symptoms are caused by structural or functional disorders in the heart. Although several studies have been conducted to identify the factors associated with the hospital readmission of patients with HF, statistics still show a high readmission rate in these patients. Therefore, it is necessary to conduct further studies to identify the factors that are effective in reducing the readmission rate and preventing the cost burden on the health system and patients. Objective: This study aims to investigate the factors associated with the 30-day readmission rate of patients with HF in Iran. Materials and Methods: This is a retrospective single-center study, which was conducted on 312 patients with HF admitted to a hospital affiliated to Isfahan University of Medical Sciences, Isfahan, Iran from April to September 2019. The medical records of these patients were reviewed and followed up for 6 months after the initial admission to assess the rate of 30-day readmission to the same hospital. The information was collected using a researcher-made form that surveyed sociodemographic characteristics, clinical characteristics, common drug treatments and discharge conditions. The data were analyzed using inferential statistics, including t-test, chi-square test/Fisher’s exact test and multiple logistic regression analysis. Results: Among patients, 181(58%) were over 65 years of age, 65.7% were male and more than 88% were married. The overall 30-day readmission rate was 7.4% (23 out of 312), and the rate of over 30-day readmission was 17% (53 out of 312). The readmission rate in men (8.8%) was higher than in women (4.7%), but this difference was not statistically significant. The readmission rate in unemployed patients (21.4%) was higher than in patients with other occupations (0.9-3.9%). The results of logistic regression showed that as body mass index increased, the likelihood of readmission decreased (OR=0.84, 95% CI, 0.74, 0.96, P=0.001), and the likelihood of readmission in patients who received diuretic therapy was 4.24 times higher than in those who did not receive diuretics (OR=4.24, 95% CI, 1.02, 1.17, P=0.047). Conclusion: The follow-up of patients with HF treated with diuretics, as well as those with high body mass index are needed due to their higher risk of hospital readmission. Developing a post-discharge care plan for these patients can be effective in reducing their 30-day readmission rate.